Analysis of Students' Misconceptions and Their Causes with a Four-Tier Diagnostic Test on Temperature and Heat Materials Assisted by Google Form in Islamic Junior High School Students - Uyuni, Qurrotul; Widodo*, Wahono; Supardi, Zainul Arifin Imam; Ilhami, Fasih Bintang; Prayogi, Ananda (Jurnal IPA & Pembelajaran IPA, 2024)
One of the problems that often occurs in learning is misconception. Students who have it must be addressed immediately because they will hinder the learning process and can cause students to experience multiple problem. Therefore, it is necessary to analyze the misconceptions that occur first. The purpose of this study was to analyze it in the temperature and heat material that occurred along with the their causes at MTs Sains Salahuddin Wahid Tebuireng. The type of research used was descriptive quantitative. The sample in this study was taken using a purposive sampling technique, namely by considering samples that had received temperature and heat material. The number of samples in this study was 22 grade 8 students. The instrument used was a four-tier diagnostic test of temperature and heat material. The results of the study showed that many students experienced misconceptions in temperature and heat material. The most common misconceptions occurred in the concept of heat transfer, where 63.63% of students were found to assume that cold temperatures in the environment were transferred to the body. Then the next most common misconception occurs in the concept of this material, where 45.45% of students assume that temperature and heat are the same thing. The cause it happen in this material is the abstract characteristics of the material and the misconceptions that teacher have